The role of laparoscopy in non-palpable undescended testicle: Analysis and review of the experience from two cities in Sudan - Sami Eldirdiri Elgaili Salah; Elssayed Osman Elssayed Ahmed (Wolters Kluwer Medknow Publications, 2022)
Introduction: It is estimated that 1%-2% of male infants have undescended testicles. The reliability of ultrasound (US) to identify the non-palpable undescended testicles (NPUDT) is controversial. Laparoscopy remains the gold standard to diagnose and manage NPUDT. Objective: The objective is to highlight the role of laparoscopy in the management of NPUDT in 2 cities from Sudan over the past decade. Materials and Methods: Patients presented to Gadarif Teaching Hospital and Almak Nimir University Hospital with NPUDT were assessed by clinical examination and US. The testis, when found during laparoscopy, was either brought down to the scrotum in a single or two-stage or removed depending on the findings. Data were collected and analysed. Results: Patients covered the age range between 18 months and 65 years. The average was 12.4. The majority, 94 (67.2%) patients were older than 5 years. The main presenting symptom was either bilateral or unilateral empty scrotum. In 12 (8.4%) patients, the main presenting symptom was primary infertility. US was done in 120 (86.6%) of the patients and failed to see the testis in more than half of them. A single-stage procedure in the form of laparoscopic search assisted with orchidopexy was achieved in 90 (62.9%) patients and orchiectomy in 13 (9.1%) patients, while in 12 (8.4%) patients the testis was not found. Other procedures were applied on the 28 (19.6%) patients who needed staged operation in the form of Fowler Stephen's, in bilateral cases, in 6 (4.2%) patients. Shehata's operation in nine patients (64%) and open orchidopexy for 8 (5.6%) patients. The post-operative complication was encountered in 14 (9.8%) of the patients in this group in the form of bleeding, vassal injury and testicular atrophy. Conclusion: Laparoscopy provides the most accurate interventional option for managing patients with NPUDT. Laparoscopic orchidopexy, whether single stage for low or 2-stages for high intra-abdominal testis, is a proven and effective extension of lap-search with minimal complications.